Analysis of influence of transnational corporations is on economy of Ukraine - Shabalina, Liudmyla; Korneychenko, Margaryta (Skhid, 2013)
This article provides an overview and analysis of the current state of operation of transnational corporations in the Ukrainian market. The examples of positive and negative impact of transnational corporations on development of Ukraine are resulted. Recommendations for development activity of domestic transnational corporations through perfection of national legislation and collaboration with foreign partners are offered